The Effect of Price and Brand Image on Repurchase Interest with Customer Satisfaction as an Intervening Variable (Case Study on Jim's Honey users in Demak District) (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This study aims to analyze the influence of price and brand image on repurchase intention with customer satisfaction as a mediating variable (a case study on users of Jims Honey products in Demak Regency). The research uses a quantitative approach, with data collected through questionnaires distributed to 138 respondents. The sampling technique used was purposive sampling. Data analysis was conducted using SmartPLS 4 software. The results show that Price has a significant effect on customer satisfaction with a p-value = 0.000 < 0.05, Brand image has a significant effect on customer satisfaction with a p-value = 0.000 < 0.05, Price does not have a direct effect on repurchase intention with a p-value = 0.238 > 0.05, Brand image has a significant effect on repurchase intention with a p-value = 0.022 < 0.05, Customer satisfaction has a significant effect on repurchase intention with a p-value = 0.000 < 0.05, Price has a significant effect on repurchase intention through customer satisfaction with a p-value = 0.034 < 0.05, Brand image has a significant effect on repurchase intention through customer satisfaction with a p-value = 0.011 < 0.05.The findings indicate that to increase repurchase intention, Jims Honey should strengthen its brand image and maintain customer satisfaction. Price also plays an important role in creating satisfaction, which in turn impacts consumer loyalty.
Keywords: Price; Brand Image; Customer Satisfaction; Repurchase Intention